Aragonite formation induced by open cultures of microbial consortia to heal cracks in concrete: Insights into healing mechanisms and crystal polymorphs. (10th November 2019) - Zhang, Jiaguang; Zhao, Cheng; Zhou, Aijuan; Yang, Chao; Zhao, Lin; Li, Zhu
Graphical abstract: Highlights: Effect of biogenic healing agents on crack-healing crystal polymorph was studied. MC-Ao based bioconcrete exhibited better healing potential. 82% of aragonite-form CaCO3 was introduced in the MC-Ao based bioconcrete. Mixed cultures resulted in a 61% decrease of production cost versus pure cultures. Abstract: Microbially induced CaCO3 precipitation (MICP), mainly in the form of calcite, has been reported to be an efficient approach for self-healing cracks in concrete. However, little is known about the implementation of aragonite, the other common crystalline form of CaCO3, in bioconcrete. Therefore, a systematic investigation of the crystal polymorphs and the healing efficiency of different cultures, i.e., two microbial consortia under anaerobic (MC-Aa) and anoxic (MC-Ao) conditions and nonureolytic pure-culture bacteria ( Bacillus cohnii ), was conducted in this study. The results showed that the MC-Ao agent exhibited the maximum values of completely healed crack widths (1.22 mm) after 28 d of healing, which is larger than the values of 0.79 and 0.73 mm for B. cohnii and MC-Aa, respectively. Field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) analyses confirmed that the biominerals induced by MC-Aa and B. cohnii are calcite, while those of MC-Ao were 82% aragonite and 18% calcite. It is noteworthy that this proportion of aragonite is the highest reported level for the MICP system to date. In addition, economic evaluation verified that the microbial consortia resulted in a 61% decrease in production costs compared to pure cultures. The intriguing findings obtained in this study may provide a scientific basis for the potential implementation of microbial consortia under anoxic conditions, such as a new self-healing agent, in bioconcrete.